A preliminary pilot scale analysis of anti-cariogenic activity of green tea powder extract flavoured with Ginger, Cloves and Mint against clinical oral pathogens. (April 2019) - Somasundaram, Rajeswari; Choraria, Ankit; George, Sruthi Merlin; Narayanaswamy, Krishnaveni; Vasudevan, Kanjana; Antonysamy, Michael; Zhang, Xiaoying
Summary: Green tea is a popular drink in Asian countries although its popularity continues to spread across the globe. Fairly, recent researchers have begun to look at the possibilities of using green tea in antimicrobial therapy, and their potential prevention of infections. The properties of green tea have shown potential for antimicrobial activity very effectively. The aim of present work is a preliminary pilot scale analysis to study the effect of anti-cariogenic efficacy of green tea extracts flavored with selective traditional medicinal plant extracts against dental carries. The green tea extracts which are rich in its anti-oxidant effect were flavored with different concentrations (1:1, 1:2, 1:3) of certain special ingredients like ginger, cloves and mint to check for its effectiveness against oral pathogens that causes caries. The results of the extractions against the isolated test oral pathogens have shown that there is a potential activity against dental pathogens. The results of this study clearly demonstrates that the minimum inhibitory concentration (MIC) ranges upon treating the test pathogens with green tea extract flavored with ginger, cloves and mint have a significant reduction of caries. In conclusion the invitro potentiality of the extracts in combination were determined to be effective in inhibiting the pathogens growth very effectively which can prevent caries and tooth decay by acting as a good anti-cariogenic and antimicrobial agent and also in future it can be taken for pilot scale level of product development with these extracts. Hence, the MIC effectiveness of the extracts against the oral pathogens were analyzed statistically using Student 't' test which shows a significant result revealing that the extracts produced 1% significance and ≥0.5% significances against dental pathogens to reduce caries and other secondary infections associated by them to maintain a healthy oral environment.